Análise de risco de cumprimento de prazo de construção comercial - BATISTA, Amanda Cremilda Lima (Universidade Federal do Pará, 2018)
Civil construction is characterized by its complexity and uncertainty, because its processes occur simultaneously and interdependently, inserted in a dynamic, non-linear and unpredictable environment. It is necessary throughout the life cycle an evaluation and management of the risk factors, thus enabling the elaboration of prevention strategies and opportunities. Therefore, this research had as objective the probabilistic evaluation of the risks in the terms of a vertical construction project, located in the city of Belém / Pa. The strategic objective of the stakeholders was the completion of the work in the 15-month period and a forecast of direct and indirect costs of R $ 8,808,614.04. In this way, the probability of the project to occur within the desired period (15 months) was evaluated through two PERT / CPM networks, called scenario 01 and scenario 02. Given that scenario 01 was developed considering the 15-month period and scenario 02 developed according to the unit composition tables of term and costs, which is called the pessimistic scenario of the work. Thus, the results of the evaluation showed that the project had a 76.79% probability of occurring in 22 months, with a possible budget increase of 35.18%, close to R $ 11,907,293.46. Therefore, the PERT / CPM methodology is satisfactory, since the objectives of this research were achieved. However, the network is incompatible with the contextual reality of the project, since construction projects have other interacting variables that influence time and costs and are impossible to evaluate with the PERT / CPM network.